IDENTIFIKASI POLA KEMITRAAN DALAM PENGEMBANGAN AGRIBISNIS KAKAO - Mursalat, Aksal; Padapi, Astrini; Wulandary, Ayu; Asra, Reza (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Cocoa development in East Luwu Regency has prospects based on the potential for production and marketing of cocoa beans. However, there are problems including productivity and low cocoa prices. To overcome these problems, it is necessary to develop cocoa agribusiness through a partnership pattern. The purpose of this study was to identify partnership patterns in cocoa agribusiness development and to determine the level of satisfaction of farmers who partnered with PT. Mars Symbioscience Indonesia. The research method is in the form of direct observation and interviews with the parties involved in the implementation of the partnership pattern, then the data is analyzed using descriptive and analysis of the level of conformity through the level of importance and level of satisfaction. The results showed that the partnership pattern in cocoa agribusiness development in East Luwu Regency was included in the plasma core pattern category, as the nucleus was PT. Mars Symbioscience Indonesia provides capital assistance, training, and training as well as marketing of the harvest, while as a plasma, cocoa farmers produce cocoa commodities. The partnership pattern activities include the upstream sector providing and providing some agricultural equipment assistance, providing seeds and experimental gardens to farmers, the farming sector providing guidance in cocoa cultivation and improving the quality of cocoa beans through harvest and post-harvest counseling and the downstream sector developing direct purchasing patterns to farmers. cocoa farmer. In addition, the level of conformity obtained from the questionnaire on the level of importance and the level of satisfaction of the partnership pattern in cocoa agribusiness development shows an average value of >100%, namely 104.78% in the very satisfied category.